Syntactic Differences Between Simple, Compound And Complex Sentences - Afrizah, Andien; Isnani, Indah Alya; Zira, Nazwa Kaila; Ismahani, Siti (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
Sentence structure plays an important role in shaping clarity, coherence, and academic accuracy in scientific writing. This study aims to examine syntactic differences in the use of simple, compound, and complex sentences in two academic essays written by EFL students. Using a qualitative descriptive research design, this study analyzes two student essays entitled “Technology: Addressing Inequality, How Technology Can Promote Inclusive Education in the Digital Revolution” and “The Impact of Electronic Media Radiation Often Overlooked by Many People”. Data were collected through document analysis and classified based on clause structure, sentence types, as well as the use of coordinating and subordinating conjunctions. The findings reveal a clear difference in syntactic patterns between the two texts. The first essay shows a strong dominance of complex and compound–complex sentences, reflecting higher syntactic complexity and analytical depth, while the second essay primarily uses simple sentences with few complex constructions, indicating a more informative and linear writing style. These differences suggest that sentence structure choices are closely related to rhetorical purposes and the level of academic literacy. The study highlights the importance of syntactic awareness in academic writing and suggests that explicit instruction on sentence variation can support EFL students in developing more sophisticated and effective written discourse.